ICT Tools for Hybrid Inquisitive Experiential Learning in Online Teaching - a case study - Haritha, Dasari; Kumar, T. Ganesh; Raju, E. Naga (Journal of Engineering Education Transformations, 2022)
The quality of engineering education plays a major role in the sustainable development of society. Efforts in designing and using interactive Information Communication Technology (ICT) tools help for stimulating curiosity among students, in particular in online teaching. It helps in creating an effective learning environment and drives students towards inquisitive and experiential learning. During COVID pandemic, it is inevitable to teach everything online and is difficult to involve student actively in learning. This paper presents a case study of designing a hybrid inquisitive experiential learning approach using teacher specific ICT tool for creating curiosity about the topic that is being learnt and its effectiveness to involve the engineering students better in learning the fundamental concepts of engineering. The end survey and assessment performance demonstrated that the use of such ICT user interface usage improved learning outcomes.